2009
DOI: 10.1159/000188660
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of the Pseudo-Glottis

Abstract: Objective: The aim of this work is to study the hitherto unclear aerodynamic parameters of the pseudo-glottis following total laryngectomy. These parameters include airflow rate, sub-pseudo-glottic pressure (SubPsG), efficiency and resistance, as well as sound pressure level (SPL). Patients and Methods: Eighteen male patients who have undergone total laryngectomy, with an age range from 54 to 72 years, were investigated in this study. All tested patients were fluent esophageal ‘voice’ speakers utilizing trache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
12
0
3
Order By: Relevance
“…Reis 17 did not detect a positive correlation between sound pressure level and air flow, that is, a strong vocal intensity does not mean that the air flow is elevated. This equilibrium consisted of a negative correlation for the proximal portion and a positive correlation for the middle and distal portions, confirming the need of this last condition for the habitual and maximum intensity.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Reis 17 did not detect a positive correlation between sound pressure level and air flow, that is, a strong vocal intensity does not mean that the air flow is elevated. This equilibrium consisted of a negative correlation for the proximal portion and a positive correlation for the middle and distal portions, confirming the need of this last condition for the habitual and maximum intensity.…”
Section: Discussionmentioning
confidence: 86%
“…16 In addition, Kotby et al 17 reported that tracheoesophageal speakers have a reduced mean air flow (53 mL/s) compared to laryngeal individuals (89 mL/s), justified by the limited supply of tracheal air that passes through the TEP, which causes a loss of aerodynamic force during phonation. Based on the manometric results of the present study, there was no significant correlation between MPT and the amplitude of esophageal and PES pressure, suggesting that there are other conditions interfering with its production and quality.…”
Section: Discussionmentioning
confidence: 99%
“…For some, the increased effort associated with TE voice production could be from elevated resistance at the neoglottis, the TE prosthesis, or both. Although the neoglottis and the prosthesis result in an overall increase in airflow resistance for individuals using TES, there are individual differences in the amount of resistance from these sources even for people with comparable TES [10,27,28]. Changes in respiratory kinematics after laryngectomy Table 5.…”
Section: Sense Of Effort When Talking Using Tracheoesophageal Versus mentioning
confidence: 99%
“…The vibrating pharyngoesophageal segment is the source of sound production and performs vocal cord function. The state of pharyngoesophageal segment made by the mucosa and surrounding fibers of the repaired cricopharyngeal, thyropharyngeal and the upper esophageal sphincter muscles is very important in voice production, and because of that it is important to preserve as much pharyngeal mucosa as possible at the time of laryngeal surgery [28]. Sometimes PE segment may be hypertonic, spastic or hypotonic.…”
Section: Esophagus and Tracheoesophageal Speech 41 Tracheoesophageamentioning
confidence: 99%